ASSESSMENT OF THE COMPETITIVENESS OF THE MARITIME TRANSPORT INFRASTRUCTURE OF UKRAINE AND EUROPEAN COUNTRIES - Vladyslav Stepanenko; Natalia Lokhman (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
The article provides an assessment of the competitiveness of the maritime transport infrastructure of Ukraine and European countries. Methods for assessing competitiveness are considered and identified as the most relevant method for assessing the competitiveness of the maritime transport infrastructure of Ukraine and European countries. The main indicators of the competitiveness of the maritime transport infrastructure have been determined for the main factors of ensuring the competitiveness of the maritime transport infrastructure. Highlighted a group of European countries, such as the Netherlands, Germany, Spain, Great Britain, France, Belgium, as they are leaders in the field of maritime transport infrastructure. Several stages were implemented to calculate the integral indicator of the maritime transport infrastructure’s competitiveness. At the first stage, the indicators were standardized, at the second, the weight coefficient of the selected indicators was calculated, at the third stage, the total rank of indicators was calculated, at the fourth stage, the weighting coefficient was calculated for each group of indicators, and at the fifth stage, the integral indicator of the competitiveness of the maritime transport infrastructure was determined. It was determined that the leaders in assessing the integral indicator of the competitiveness of the maritime transport infrastructure are Great Britain (8.13), Germany (7.78), and Belgium (7.07).Ukraine has the lowest rate (4.7).Also, it was found that the most influential are external factors, such as economic, legal, political, social, technological, environmental, integration, institutional (Ukraine — 2.65; Netherlands — 2.87; Germany — 2.07; Spain — 2,19; Great Britain — 1.87; France — 2.16; Belgium — 3.22).The main directions of increasing the competitiveness of the Ukrainian maritime transport infrastructure are proposed, taking into account the experience of the leading countries.